Association of aneurysms and variation of the A1 segment. (23rd April 2013) - Krasny, A; Nensa, F; Sandalcioglu, I E; Göricke, S L; Wanke, I; Gramsch, C; Sirin, S; Oezkan, N; Sure, U; Schlamann, M
Abstract : Background and purpose: Previous studies have described a correlation between variants of the circle of Willis and pathological findings, such as cerebrovascular diseases. Moreover, anatomic variations of the anterior cerebral artery (ACA) seem to correspond to the prevalence of aneurysms in the anterior communicating artery (ACoA). The aim of this study was to assess the prevalence of aneurysms in patients with anatomical/morphological variations of the circle of Willis. Methods: We retrospectively analyzed 223 patients who underwent cerebral angiography between January 2002 and December 2010 for aneurysm of the ACoA. Diagnostic imaging was reviewed and statistically evaluated to detect circle of Willis anomalies, aneurysm size, and rupture. 204 patients with an unrelated diagnosis served as the control group. Results: Variations of the A1 segment occurred significantly more frequently in the aneurysm group than in the control group. Mean aneurysm size in patients with grades I and III hypoplasia or aplasia was 6.58 mm whereas in patients with grade II hypoplasia it was 7.76 mm. Conclusions: We found that variations in the A1 segment of the ACAs are correlated with a higher prevalence of ACoA aneurysms compared with patients with a symmetric circle of Willis.